THE HISTORY AND IMPORTANCE OF THE ENGLISH LANUAGE - Risqulova Charos, (TADQIQOTLAR, 2026)
Annotation This article analyzes the historical development of the English language based on specific dates and statistical facts. It examines key historical events such as the migration of Germanic tribes in the 5th century, the Norman Conquest of 1066, the introduction of the printing press in 1476, the expansion of the British Empire, and the rise of the United States in the 20th century. The article also presents statistical data demonstrating the global importance of English in science, technology, the Internet, and international relations.